Teachers’ language use in United Kingdom Chinese community schools: Implications for heritage-language education - Yiakoumetti, Androula (Frontiers in Psychology, 2022)
This study deals with teachers’ language use as it is manifested in community-based heritage-language classes. Specifically, it focuses on the functions of students’ dominant variety (L1, English) when harnessed by teachers for the purposes of teaching their ethnic language (L2, Mandarin Chinese). Empirical investigation was conducted at two Chinese community schools in the United Kingdom and data demonstrate that students’ L1 was utilised naturally and systematically by teachers to facilitate students’ L2 learning. Various L1 facilitative functions were identified and these generally accord well with functions recorded in other studies. In addition, this study underlines the potentially unique characteristics of community-based heritage-language education: while the target variety of students (Mandarin Chinese) is routinely the native variety of teachers, teachers struggle to explain new linguistic information in Mandarin because of students’ low proficiency while they concurrently struggle with at least some elements of students’ native or dominant variety (English). Teachers explained that the fact that students’ dominant language of English is a global language makes their use of it all the more likely. Teachers demonstrated a strong tendency to feel ill-prepared for their language teaching role. There is thus a clear need for heritage-language teachers to receive training that is sociolinguistically informed. This training should emphasise the potential utility of exploiting students’ full linguistic repertoires by drawing in particular on the crosslinguistic similarities and differences between the varieties of which students are cognisant. Teacher-training programmes that promote such awareness may well hold the key to better heritage-language education which will continue to have a crucial role in maintaining and developing minority community languages.